From Uswah to Habitus: Transformation of Religious Character Through Example in Madrasah - Moch Tohet; Ramanda Satria Rodmaya; Homaidi Homaidi (Nurul Jadid University, 2025)
This study aims to examine the role of teacher role models as an effective strategy in shaping the religious character of students. Departing from the phenomenon of moral degradation among adolescents, character education based on religious values is seen as an urgent need, especially in the madrasah environment. This study employs a descriptive, qualitative approach using a case study method. Data were collected through observation, in-depth interviews, and documentation, and then analyzed using Miles and Huberman's models. The results of the study show that the example of teachers in daily worship activities, commemoration of Islamic holidays, habituation of good character, and social interaction have a tangible impact on the formation of students' religious character. Teachers who consistently exhibit religious behaviors, such as congregational prayers, reciting the Qur'an, offering greetings, and being fair and empathetic, are able to instill Islamic values through a natural internalization process. The implications of this study suggest that Islamic educational institutions should prioritize exemplary behavior as the primary strategy in designing character-building programs and integrate them into the overall school culture to create a consistent and sustainable religious environment.